FTA and Markov Analysis Comparison Applied to N219 Aircraft Hydraulic System based on Fail to Generate Hydraulic Power - Yoga Yulasmana (Akademi Angkatan Udara, 2021)
In general, this paper contained a safety assessment conducted on the N219 Aircraft hydraulic system to ensure that its systems meet the safety requirements. Further, the safety requirements will be established by the aviation authority as a certification basis for satisfying the CASR Part 23 according to the N219 category as a commuter aircraft. To conduct a safety assessment process on this system, this paper follows the process outlined in SAE ARP4761 document. It encompasses Functional Hazard Assessment (FHA), Preliminary System Safety Assessment (PSSA), and System Safety Assessment (SSA). Afterward, this paper will focus on quantitative analysis for SSA process based on fail to generate hydraulic power failure condition. In particular, the quantitative analysis for this process will use Fault Tree Analysis (FTA) and Markov Analysis (MA) to make a comparative evaluation. Since N219 Aircraft still in the phase of getting a Type Certificate, the comparative results obtained from both methods can be taken into consideration in the development of the N219 Aircraft for the military version. Furthermore, the quantitative analysis comparison results from this paper are expected to be applied to other failure conditions due to modification or additional components of the N219 Aircraft existing system.